Analisis Risiko Operasional Jasa Pengiriman Selama Pandemi Covid-19 - Kulsaputro, Januar; Bahri, Syamsul; Asmal, Sapta (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2022)
Abstract This study aims to (1) determine the priority risk sources experienced by TIKI Makassar Branch due to the Covid-19 pandemic. (2) identify and design possible handling strategies so as to minimize operational risks experienced by TIKI Makassar Branch.This research was conducted at the TIKI Boulevard Makassar branch using the HOR ( House of Risk ) method approach to find out the priority risk sources based on the ARP ( Aggregate Risk Potential) value and design a risk/mitigation management strategy by measuring the ETD k value ( Effectiveness To Difficulty Ratio ). from the highest to the lowest value. Based on the results of the analysis, it is concluded that the highest priority risk sources that become problems and can disrupt the company's operations are human resources who are not careful, data errors from the previous process, package recipients who do not understand the rules, knowledge of the types of goods that are lacking and means of transportation disturbed. There are several handling strategies that can be applied in dealing with priority risk sources, namely tightening supervision of employee activities, maintaining good communication between departments/departments, improving workflows between sections/departments, tightening SOP regulations regarding sanctions, providing training/training for employees, conducting negotiating with partner airlines, and providing explanations to consumers about the workflow of shipping goods. Keywords: Risk Management, HOR (House of Risk), ARP (Aggregate Risk Potential), ETD k (Effectiveness To Difficulty Ratio), Priority Risk, Mitigation.